2010
DOI: 10.1111/j.1747-0285.2009.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of Purine Nucleoside Phosphorylase Multisubstrate Analogue Inhibitors Containing Difluoromethylene Phosphonic Acid against Leukaemia and Lymphoma Cells

Abstract: Potent inhibitors of purine nucleoside phosphorylase (PNP) are expected to act as selective agents against T‐cell tumours. Five compounds with guanine, three with hypoxanthine, and five with 9‐deazaguanine, all connected by a linker with difluoromethylene phosphonic acid, were studied on their inhibitory potential against human and calf PNPs. Antiproliferative activity of these analogues against lymphocytes as well as lymphoma and leukaemia cells has been also investigated. All tested compounds act as multisub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Finally, we tested whether other PNP inhibitors might induce death of SAMHD1-deficient cells in the presence of dG. Indeed, BMDMs showed reduced viability upon exposure to either homo-DFPP-DG or 6C-DFPP-DG (Glavas-Obrovac et al, 2010;Hikishima et al, 2007Hikishima et al, , 2010 together with low doses of dG (Figures 4M and 4N). Taken together, these data show that SAMHD1 protected cells against death that was synergistically induced by PNP inhibitors and dG.…”
Section: Samhd1 Protects Against Combined Forodesine and Dg Treatmentmentioning
confidence: 99%
“…Finally, we tested whether other PNP inhibitors might induce death of SAMHD1-deficient cells in the presence of dG. Indeed, BMDMs showed reduced viability upon exposure to either homo-DFPP-DG or 6C-DFPP-DG (Glavas-Obrovac et al, 2010;Hikishima et al, 2007Hikishima et al, , 2010 together with low doses of dG (Figures 4M and 4N). Taken together, these data show that SAMHD1 protected cells against death that was synergistically induced by PNP inhibitors and dG.…”
Section: Samhd1 Protects Against Combined Forodesine and Dg Treatmentmentioning
confidence: 99%
“…Finally, we tested whether other PNP inhibitors might induce death of SAMHD1-deficient cells in the presence of dG. Indeed, BMDMs showed reduced viability upon exposure to either homo-DFPP-DG or 6C-DFPP-DG (Glavas-Obrovac et al, 2010; Hikishima et al, 2007, 2010) together with low doses of dG (Figure 4M,N). Taken together, these data showed that SAMHD1 protected cells against death that was synergistically induced by PNP inhibitors and dG.…”
Section: Resultsmentioning
confidence: 99%
“…Another series of guanine analogues 199–203 (Fig. ) containing a branched aliphatic chain terminated with the α , α ‐(difluoromethylene)phosphonate group was confirmed to be the multisubstrate PNP inhibitors with activities ranging from 7.2 to 15 nM . Very potent PNP inhibitors among the ANPs represent the 9‐deazaguanine analogues 204–208 (Fig.…”
Section: Acyclic Nucleoside Phosphonatesmentioning
confidence: 93%
“…48) containing a branched aliphatic chain terminated with the α,α-(difluoromethylene)phosphonate group was confirmed to be the multisubstrate PNP inhibitors with activities ranging from 7.2 to 15 nM. 182 Very potent PNP inhibitors among the ANPs represent the 9-deazaguanine analogues 204-208 ( Fig. 48), designed by Yokomatsu et al 183 Among them, 9 -(5,5 -difluoro-5 -phosphonopentyl)-9-deazaguanine (DFPP-DG, 205) possesses subnanomolar activities measured on calf PNP (K i = 85 pM) and is almost as potent as the transition state inhibitors immucillins, [184][185][186][187] for example, immucillin H 209 (K i = 23 pM, calf PNP).…”
Section: Anps With Fluorine Atom(s) At Phosphonate α-Carbonmentioning
confidence: 94%